Intensification of social behavior in community development: An approach to applied social psychology - Sulistio, Sulistio (Journal of Advanced Guidance and Counseling, 2023)
Purpose - This article aims to: First, identify social behavior in community development both as knowledge and action. Second, analyzing social behavior in community development through an applied social psychology approach.Method - research type used library research.Result - The results of the discussion show: First, today's social behavior in community development is facing various challenges along with the social dynamics themselves. In order to maintain and develop the existence of community development, it is necessary to involve other scientific disciplines. The involvement of other scientific disciplines, one of which is intended in an effort to intensify social behavior in the development of society itself. Second, the applied social psychology approach can be used in the realm of understanding social problems, identifying factors that influence social attitudes and behavior, interventions, designing social change, and evaluating activity programs.Implications - This study the impact on the development of applied social psychology approaches can be applied to the realm of understanding social problems, identifying factors that influence social attitudes and behavior, interventions, designing social change, and evaluating activity programs. In addition, applied social psychology can also be used as an approach in strengthening attitudes and behavior in intensifying community development.Originality - This research is strengthening intensification of social behavior in community development to applied social psychology.***Tujuan - Artikel ini bertujuan: Pertama, mengidentifikasi perilaku sosial dalam pengembangan masyarakat baik sebagai pengetahuan maupun tindakan. Kedua, menganalisis perilaku sosial dalam pengembangan masyarakat melalui pendekatan psikologi sosial terapan.Metode - jenis penelitian yang digunakan adalah penelitian kepustakaan.Hasil - Hasil pembahasan menunjukkan: Pertama, perilaku sosial masyarakat dewasa ini menghadapi berbagai tantangan seiring dengan dinamika sosial itu sendiri. Dalam rangka menjaga dan mengembangkan keberadaan pengembangan masyarakat, perlu melibatkan disiplin ilmu lain. Keterlibatan disiplin ilmu lain, salah satunya dimaksudkan dalam upaya mengintensifkan perilaku sosial dalam pembangunan masyarakat itu sendiri. Kedua, pendekatan psikologi sosial terapan dapat digunakan dalam ranah memahami masalah sosial, mengidentifikasi faktor-faktor yang mempengaruhi sikap dan perilaku sosial, intervensi, merancang perubahan sosial, dan mengevaluasi program kegiatan.Implikasi - Studi ini memiliki dampak terhadap pengembangan pendekatan psikologi sosial terapan dapat diterapkan pada ranah pemahaman masalah sosial, mengidentifikasi faktor-faktor yang mempengaruhi sikap dan perilaku sosial, intervensi, merancang perubahan sosial, dan mengevaluasi program kegiatan. Selain itu, psikologi sosial terapan juga dapat digunakan sebagai pendekatan dalam penguatan sikap dan perilaku dalam mengintensifkan pembangunan masyarakat.Orisinalitas - Penelitian ini memperkuat intensifikasi perilaku sosial dalam pengembangan masyarakat terhadap psikologi sosial terapan.